The Effect of the Pancasila Student Profile Strengthening Project of the Merdeka Curriculum on the Critical Thinking Skills of Grade IV Students at SD Negeri 1 Pagar Alam - Sabilla, Suci Lela Sabilla; M. Agus Maryanto (The Future of Education Journal, 2025)
This research is motivated by the suboptimal critical thinking abilities of students in facing the challenges of learning. The aim of this study is to determine whether there is an influence, and to what extent, the P5 of the Merdeka Curriculum affects the critical thinking abilities of grade IV students at SD Negeri 1 Pagar Alam City for the 2024/2025 academic year. This study uses a descriptive quantitative approach with a population of 128 students and a sample of 57 students. The sampling technique used is Probability Sampling with Simple Random Sampling, and data collection techniques include observation, questionnaires, and documentation. Data analysis was carried out through validity testing, reliability, normality, linearity, simple linear regression, correlation coefficient, determination coefficient, and t-test using SPSS 26 software. The results indicate a positive and significant effect of the P5 project implementation on students' critical thinking skills, with a significance value of 0.000 < 0.05. The effect of P5 on students' critical thinking skills is 22.3%, showing a significant contribution to improving students' critical thinking abilities. It can be concluded that there is an effect of the P5 Project of the Merdeka Curriculum on the critical thinking skills of grade IV students at SD Negeri 1 Pagar Alam.